'SS Mendi: Shaping the Nation' in SEK Mqhayi's Ukutshona kuka Mendi: The sinking of the Mendi (1922) and the Narrative of Catastrophe in Hilary Graham's The Wreck of the Mendi (1994). Issue 1 (2nd January 2019) - Smith, Neville James
Abstract : This article examines how a poem and a painting, which both refer to the wreck of the troopship SS Mendi on 21 February 1917, offer different insights into the way they entered a fractured national memory, culture and history. SEK Mqhayi's traditional poem Ukutshona kuka Mendi: The sinking of the Mendi and Hilary Graham's painting The Wreck of the Mendi reveal how narratives reflected on the relationship between Europe and Africa in 1917. They also show how such links have changed as revealed in the recent centenary celebrations of the SS Mendi disaster in Britain and South Africa. The reciprocity between a traditional African culture and a settler ethos is examined as well as how this plays a part in the creation of new meaning. This article explores the way art may inform and unite cultures at different historical junctures.